EFFECT OF ATMOSPHERIC MASSES ON THE SPECTRAL INTENSITY OF SOLAR RADIATION - Nikitin, B.; Mayorov, V.; Kharchenko, V. (Energy and Automation, 2016)
The effect of the atmospheric mass on the way to the sunlight receiving surface on the spectral characteristics of solar radiation in the atmospheric layer under consideration AM 1.5 as a filter having appropriate transmittance for the corresponding wavelength.